Anaemia: female youth’s knowledge and supplementation program management - Khomsan, Ali; Riyadi, Hadi; Prasetya, Guntari (Intelektual Pustaka Media Utama, 2025)
The prevalence of anaemia among adolescent girls in Indonesia is 18.4%. One of the main indicator targets is reducing the prevalence of anaemia is in the form of iron-folic acid (IFA) supplementation for adolescent girls. The research aims to analyze knowledge of female youth on anaemia and management of iron-folic acid supplementation. This study used a cross-sectional design, and it was conducted in 24 senior high schools in Cianjur Regency (high stunting area) and Depok City (low stunting area). The total sample of this study was 243 female youth. The study began from September 2019 to February 2020 for the 1st term and continued from October 2022 to March 2023 for the 2nd term. The quantitative result showed that there was a significant difference in knowledge about the frequency of providing the iron-folic acid supplement (IFAS) at school and the duration in a year that students must consume the IFAS between high stunting and low stunting (p=0.000). A significant proportion of female youth, 67.5% in high stunting areas and 71.7% in low stunting areas, exhibit insufficient nutrition knowledge, underscoring the necessity for a nutrition education initiative targeting high school students. The qualitative results showed the input-process-output of the IFA program have been administered for the last few years, providing several constraints in order to improve the IFA program management. Based on those findings, the IFA supplementation program provides a potential chance for addressing anaemia in female youth.